Optimization of thermopressing conditions for the production of binderless boards from a coriander twin‐screw extrusion cake. Issue 13 (10th December 2016) - Uitterhaegen, E.; Labonne, L.; Merah, O.; Talou, T.; Ballas, S.; Véronèse, T.; Evon, Ph.
ABSTRACT: A deoiled press cake resulting from twin‐screw extrusion of coriander fruits was used as a raw material for the production of self‐bonded boards. The operating parameters for thermopressing were varied and include the applied pressure (19.6–39.2 MPa), molding time (60–300 s), and molding temperature (155–205 °C). The optimized process conditions (21.6 MPa, 300 s, 205 °C) resulted in a board with a density of 1323 kg/m 3, a flexural strength of 23 MPa, a modulus of elasticity of 4.4 GPa, and a thickness swelling of 31%. The thickness swelling was effectively reduced to 20% through the application of a heat treatment at 200 °C after thermopressing. A variation of the moisture content of the press cake between 3 and 8% showed that increased moisture contents do not lead to improved mechanical properties of the resulting board and further induce internal fracturing of the board during thermopressing. The manufactured binderless boards may act as environmentally friendly alternatives to commercial wood‐based boards such as oriented strand board and particleboard. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44650. Abstract :